Osmotic Dehydration Pretreatment with Panela for the Production of Apple Snacks. - QUINDE-MONTERO, HENRY JESÚS; SANCHEZ-CHERO, MANUEL JESUS; FLORES-MENDOZA, LESLY CAROLINA; MIRANDA-ZAMORA, WILLIAM ROLANDO; SANCHEZ-CHERO, JOSE ANTONIO; VERA-JIMENEZ, WILLIAM; GUTIERREZ-SEGURA, FLABIO; MOSCOL-CALDERON, CRISTHIAM ALBERTO; ORTIZ-GARCÍA, LUCERITO KATHERINE (Current Research in Nutrition & Food Science, 2025)
Osmotic dehydration removes water from fruits using hypertonic solutions, enhancing shelf life and quality. However, little research explores natural sweeteners like panela as osmotic agents in developing nutritious, acceptable apple-based snack products. The objective of this research was to evaluate the effect of osmodehydration pretreatment with panela in development of apple snacks (Malus domestica). The methodology evaluated was through an osmotic dehydration process of apple. Panela syrups were used at concentrations of 45 °Brix and 50 °Brix with immersion times of 120 and 180 minutes and followed by drying for 8 hours at 55 °C. Sensory evaluation was performed with student as participants using five-point hedonic scale. For the previously mentioned data analysis, a completely randomized design (CRD) with a 2x2 factorial setup was employed, whereas a five-point hedonic scale was utilized for the sensory evaluation. Using a 2x2 factorial statistical design, it was possible to determine p-values < 0.05, indicating a significant level of confidence in the effects of concentration and temperature on water loss (WL), weight reduction (WR), and solids gain (SG). Results showed weight loss (WR) which was 30.28% and water losses (WL) of up to 31.87%. On the other hand, the lowest solids gain was 2.60% while the highest was 5.64 Finally, the sensory analysis showed that the samples pretreated with osmodehydration T4 (50 °Brix-180 min) and T3 (45 °Brix-180 min) had higher acceptability, likewise the least accepted by the panela were T1, S/T (without treatment) and T2 in descending order.